Evaluation of different methods of environmental enrichment to control anxiety in dogs undergoing hemilaminectomy after acute intervertebral disc extrusion: a randomized double-blinded study - Pennington, Ellery; Springer, Cary; Albright, Julia; Castel, Aude (Frontiers in Veterinary Science, 2023)
Objective The goal of this randomized, double-blinded, placebo-controlled study was to evaluate the effect of environmental enrichment (EE) on post-operative pain and anxiety in dogs following hemilaminectomy for acute intervertebral disc extrusion (IVDE). Methods Twenty healthy client-owned dogs undergoing a hemilaminectomy for IVDE with the same immediate post-operative analgesia protocol were randomly assigned to either the EE or standard environment (SE) group post-operatively. Recovery was achieved in an intensive care room (SE) or a separate quiet room (EE) equipped with white noise and classical music. EE dogs were also exposed to dog-appeasing pheromones, essential oil scents, and positive human interactions and were provided meals through food toys. A blinded evaluator assessed all dogs using the modified Glasgow Composite Pain Scale (mGCPS) on presentation and at several time points post-operatively. A rescue injection of the opioid methadone was given to the dogs with an mGCPS score of ≥5/20. Dogs received the antidepressant trazodone when anxious behaviors (5 mg/kg) were observed. The mGCPS scores, the latencies to receive the first methadone and trazodone doses and to eat the first meal, the number of methadone and trazodone doses, and the number of meals ingested in the first 24 and 48 h post-surgery were compared using Wilcoxon tests, and Benjamini–Hochberg correction for false discovery rate was applied. Results Although median mGCPS scores did not differ between the groups, compared to SE dogs (n = 10), EE dogs (n = 6) received trazodone earlier (p = 0.019), were administered fewer methadone injections at 24 h (p = 0.043), and ate more at 48 h post-surgery (p = 0.007). Therefore, EE and anti-anxiety medications could be beneficial in improving the wellbeing of dogs post-operatively.